Who talks about climate, peace and security: A social media analysis to identify key global actors - Bioversity International and International Center for Tropical Agriculture (CIAT) (2025)
This carousel explains who shapes the global conversation on climate, peace, and security, and what that means for whose voices are heard. It presents findings from a social media analysis of thousands of posts on climate security shared on Twitter (now X) between 2014 and 2022. The carousel shows how attention to climate security surged after key UN policy moments, particularly following the Sustaining Peace Framework and debates at the UN Security Council. It then maps the most influential actors driving the discussion, revealing that research institutions, think tanks, and Global North organizations dominate the network. While these groups are well connected internally, the analysis shows limited dialogue across communities and a clear underrepresentation of Global South voices. The carousel argues that closing this gap is essential, since people most affected by climate-related insecurity are often missing from the conversation, and highlights opportunities to build more inclusive, bottom-up climate security dialogue